Pollution in textbooks from 16 countries : socio-economic and ethical issues; individual or social responsibility? - Ferreira, Cláudia (2008)
In this study it was intended to analyse the progression of the socio-economic and ethical dimensions within the topic pollution, in the textbooks of 16 countries, along their school system, by looking at the Socio-economic and Ethical Dimensions as well as at the Approaches to solve pollution problems, within the conception Individual vs social. In this work we analysed textbooks from sixteen countries from Europe (West to East: Portugal, France, Italy, Malta, Germany, Hungary, Poland, Romania, Lithuania, Estonia, Finland, Cyprus), from Africa (Senegal, Morocco, Tunisia) and from the Middle East (Lebanon), since the first grade till the end of the secondary school. We used a grid constructed in the context of a European Project “Biohead Citizen” (“Biology Health and Environmental education for better citizenship” STREP, CIT2-CT2004-506015, Carvalho et al. 2004). About socio-economical end ethical issues, results showed that: i) these dimensions are completely absent in the textbooks of 6 of the 16 analysed countries; ii) among the countries where both dimension are present (predominantly in the Western European countries), the Socio-economic dimension is consistently more present than the Ethical one. Concerning the Approaches to solve pollution problems, countries that highlight changes in technologies in detriment of changes in individual behaviour are also the same ones that give more attention to socio-economic and ethical controversies.